Lower endoscopic delivery of freeze-dried intestinal microbiota results in more rapid and efficient engraftment than oral administration - Christopher Staley; Hossam Halaweish; Carolyn Graiziger; Matthew J. Hamilton; Amanda J. Kabage; Alison L. Galdys; Byron P. Vaughn; Kornpong Vantanasiri; Raj Suryanarayanan; Michael J. Sadowsky; Alexander Khoruts (Scientific Reports, 2021)
Abstract Fecal microbiota transplantation (FMT) is a highly effective treatment for recurrent Clostridioides difficile infection (rCDI). However, standardization of FMT products is essential for its broad implementation into clinical practice. We have developed an oral preparation of freeze-dried, encapsulated microbiota, which is ~ 80% clinically effective, but results in delayed engraftment of donor bacteria relative to administration via colonoscopy. Our objective was to measure the engraftment potential of freeze-dried microbiota without the complexity of variables associated with oral administration. We compared engraftment of identical preparations and doses of freeze-dried microbiota following colonoscopic (9 patients) versus oral administration (18 patients). Microbiota were characterized by sequencing of the 16S rRNA gene, and engraftment was determined using the SourceTracker algorithm. Oligotyping analysis was done to provide high-resolution patterns of microbiota engraftment. Colonoscopic FMT was associated with greater levels of donor engraftment within days following the procedure (ANOVA P = 0.035) and specific increases in the relative abundances of donor Lachnospiraceae, Bacteroidaceae, and Porphyromonadaceae (P ≤ 0.033). Lower relative abundances of Bacteroidaceae, Lachnospiraceae, and Ruminococcaceae families were associated with clinical failures. These results suggest that further optimization of oral capsule FMT may improve its engraftment efficiency and clinical efficacy.